Generation and Composition of Domestic Solid Waste in Vinh Chau Town, Soc Trang Province, Vietnam - Giao , Nguyen Thanh; Son Phuc (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2023)
The study aims to assess the generation, composition and household’s management of domestic solid waste in Vinh Chau town, Soc Trang province, Vietnam. The required data were collected by field survey and by interviewing 198 households in the study area. The results showed that the average generation rate of solid wastes was 2.29 kg/day with an emission factor per capita of 0.55 kg/person/day. The composition of domestic solid wastes was organic matters accounted for 86.60%, plastics 4.30%, hazardous waste 2.11%, paper and cardboard 1.95%, textiles 1.29%, metals 0.97%, brick and porcelain 0.54%, glass 0.51% and other components 1.73%. The solid wastes are now not classified at source. About 46.46% of the surveyed households have registered for the solid waste collection service and the collection rate in the study area is only 56.5%. The result also presented that 53.53% of waste is collected and brought to the landfill for treatment, while the remaining is mainly burned by the households. Solid waste management in the study area has several limits and it should be soon improved to meet the current legal regulations.